Climate change impacts on socioeconomic activities through labor productivity changes considering interactions between socioeconomic and climate systems. (10th April 2019) - Matsumoto, Ken'ichi
Abstract: While human socioeconomic activity leads to climate change, the latter also affects the former; socioeconomic and climate systems have considerable interactions. Some studies have looked at the effects of climate change on labor productivity and gross domestic product, yet they have not considered the interaction between socioeconomic and climate systems. This study therefore examined that aspect as well as the economic impact of climate-change-induced labor productivity change. Business-as-usual and two emissions reduction scenarios—2°C and Representative Concentration Pathway 4.5—were adopted. Data analysis employed a computable general equilibrium model and a simple climate model. The results show that global economic impacts of climate-change-induced labor productivity change have not been large. A negative effect on economic activities was found when the relationship between climate change and labor productivity was considered in the economic model. Although such impacts were larger in the business-as-usual scenario, that was not the case in the 2 °C scenario. The results suggest that greater levels of climate change are in accordance with greater socioeconomic impact at the global level. In particular, impact on high-temperature regions was found to be considerable. Interestingly, not all regions experienced economic loss from climate change. Some in the low- to medium-temperature zones received a positive economic effect because of comparative advantage caused by differences in labor productivity changes among regions. The coupled modeling scheme ultimately was effective in evaluating the interaction. Expanded assessment of climate change, mitigation, and adaptation will aid further understanding of the interaction of climate change and socioeconomic activities. Graphical abstract: Image 1 Highlights: Economic impact of climate-change-induced labor productivity change was assessed. A model considering interaction between human and climate systems was applied. The model considered the relationship between labor productivity and temperature. The global economic impact owing to labor productivity change was found to be low. Negative impacts were large for hot regions, though some received positive impacts.